PENGARUH MEDIA PEMBELAJARAN BERBASIS CANVA TERHADAP MOTIVASI BELAJAR SISWA KELAS VI SD - Hernawati; Babang Robandi; Sukaesih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explore the impact of using Canva-based learning media on the learning motivation of fourth-grade elementary school students. Canva enables teachers and students to create engaging visual learning materials, enhancing comprehension and student engagement. The study employs a quantitative approach with an experimental design. Results show that using Canva significantly boosts students' learning motivation compared to conventional teaching methods. Additionally, Canva fosters social interaction, collaboration, and creativity among students. These findings suggest that Canva is an effective tool for creating engaging and meaningful learning experiences.